Prediction method of soil horizontal displacement caused by non-uniform distribution of disturbance force in shield construction - Bao-xin Jia; Zong-xian Gao; Hong-yan Hua (Canadian Science Publishing, 2023)
Based on the Mindlin solution, this paper considers the influence of factors such as the non-uniform distribution of additional thrust of the cutter head influenced by lateral earth pressure in shield excavation, the non-uniform distribution of friction of shield shell influenced by soil softening and slurry spreading, and the non-uniform distribution of grouting pressure influenced by slurry spreading on the horizontal displacement of soil. The existing prediction formula is revised and verified by engineering examples. It is found that: affected by the shield construction disturbance force, the horizontal displacement behind the excavation surface is larger than that in front of the excavation surface, and the peak value of the horizontal displacement appears around the tunnel axis; through the verification of engineering case, when calculating the horizontal displacement in front of the excavation surface, the calculation results of both the modified formula and the original formula are in good agreement with the measured values, which can reflect the change trend of the measured horizontal displacement; when calculating the horizontal displacement behind the excavation surface, the calculation result of the existing formula has a great error due to the assumption of uniform distribution of disturbance force, which is different from the law of the measured result; the calculation result of the modified prediction formula is obviously in better agreement with the measured deformation value, and the error is smaller, which is more in line with the engineering reality.